2011
DOI: 10.1111/j.1095-8649.2011.03043.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in location and morphology of chloride cells during early life stages of the Nile tilapia Oreochromis niloticus adapted to fresh and brackish water

Abstract: Ontogenetic changes in the location, size, density and morphology of chloride cells in the Nile tilapia Oreochromis niloticus adapted to fresh and brackish water are described using Na(+) /K(+) -ATPase immunohistochemistry, light microscopy (LM), scanning electron microscopy (SEM) and confocal scanning laser microscopy (CSLM). The pattern of chloride cell distribution changed during development under both treatments, with chloride cell density decreasing significantly from hatch to 7 days post-hatch, but appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The significant decrease in overall MRC density following transfer to elevated salinities reported here is in agreement with previous studies which reported a decrease in density of total MRCs following seawater adaptation in gills of the adult Mozambique tilapia (van der Heijden et al, ; Lin and Hwang, ) and yolk‐sac larvae of the Nile tilapia (Fridman et al, ). However, conflicting results do exist in the literature concerning the overall density of MRCs in hypotonic and hypertonic environments.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The significant decrease in overall MRC density following transfer to elevated salinities reported here is in agreement with previous studies which reported a decrease in density of total MRCs following seawater adaptation in gills of the adult Mozambique tilapia (van der Heijden et al, ; Lin and Hwang, ) and yolk‐sac larvae of the Nile tilapia (Fridman et al, ). However, conflicting results do exist in the literature concerning the overall density of MRCs in hypotonic and hypertonic environments.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed the ontogeny of osmoregulatory capability in early life stages of teleosts is characterized by a distinct spatial shift in MRC distribution. It is generally accepted that integumental MRCs are initially responsible for osmoregulation prior to development of the adult osmoregulatory organs in O. mossambicus (Ayson et al, 1994;Shiraishi et al, 1997;Hiroi et al, 1999), O. niloticus (Fridman et al, 2011), and F. heteroclitus (Katoh et al, 2000) and, similarly, density diminishes with age in P. olivaceus (Hiroi et al, 1999), disappearing completely in adulthood (Whitear, 1970;Bullock and Roberts, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the morphology changes have to be made to maintain water and ion balance. Based on these results, we speculated that the changes in density and morphology of chloride cells caused by increased salinity help adapt to high-salinity conditions (Fridman et al 2011). An ultra-structural hallmark of the seawater chloride cells is an invagination called apical crypt, which structure is correlated with adaptation to high salinities (Carmona et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…The tail section of the larvae was chosen because it proved easier to cut into ultrathin sections than the yolk‐sac, as previous attempts to cut through the thicker yolk‐sac had resulted in poor sectioning, with the epithelium lifting away from the yolk mass. Previous studies in the Nile tilapia had demonstrated that MRCs were present on the tail in meaningful and measureable numbers from 3 dph onward (Fridman et al, ), therefore, this area was regarded as representative of integumental MRCs. Ultrathin sections (90 nm) were cut from each of the dissected tails and serial sections were made every 10 µm thereafter.…”
Section: Methodsmentioning
confidence: 99%